Development of E-Module of Teacher Professional Ethics Based on Team-Based Project with Onenote Office 365 - Permana, Dian Fithra; Muhsin, Muhsin; Saeroji, Ahmad; Afianingsih, Lia (Dinamika Pendidikan, 2021)
This research revealed the effectiveness of e-module based on team-based project on teacher profession ethics in supporting online learning. This research was a development research with ADDIE.  The e-module of Teacher Professional Ethics was developed based on OneNote application. The feasibility level obtained by the media from the average material validation result was 3.00 with a good category and the results of validation media obtained an average of 3.44 with a very good category. E-module learning media trials for students gained an average eligibility of 3.30 with a good category. Thus, it can be concluded that the learning media e-module of teacher professional ethics with Onenote Office365 in the Administrative Education study program can be used to improve knowledge and alternative online learning during the Covid-19 pandemic.